Influence of the Efavirenz Micronization on Tableting and Dissolution - Lucio Mendes Cabral; Valeria Pereira de Sousa; Helvécio Vinícius Antunes Rocha; Valéria Sant'Anna Dantas Esteves; Carlos Rangel Rodrigues; Rita de Cássia da Silva Ascenção Barros; Helena Carla Rangel Castro; Thiago da Silva Honório; Flávia Almada do Carmo; Eduardo Costa Pinto (MDPI AG, 2012)
The purpose of this study was to propose an analytical procedure that provides the effects of particle size and surface area on dissolution of efavirenz. Five different batches obtained by different micronization processes and with different particle size distribution and surface area were studied. The preformulation studies and dissolution curves were used to confirm the particle size distribution effect on drug solubility. No polymorphic variety or amorphization was observed in the tested batches and the particle size distribution was determined as directly responsible for the improvement of drug dissolution. The influence of the preparation process on the tablets derived from efavirenz was observed in the final dissolution result in which agglomeration, usually seen in non-lipophilic micronized material, was avoided through the use of an appropriate wet granulation method. For these reasons, micronization may represent one viable alternative for the formulation of brick dust drugs.